Accounting Principles, Chapters 1-13 - J.Weygandt Jerry (Wiley, 2001)
Before you buy, make sure you are getting the best value and all the learning tools you’ll need to succeed in your course. If your professor requires eGrade Plus, you can purchase it now at no additional cost!